Improving student chemistry laboratory performance through Nyamplung ethnoscience-oriented learning of the Sasak tribe - Khery, Yusran; Hakim, Aliefman; Rokhmat, Joni; Sukarso, Aa (Eclética Química, 2025)
Evaluating student performance in open-ended laboratory settings presents challenges compared to the structured format of typical lab exercises, which often resemble recipes. This study aims to enhance student performance by integrating local ethnoscience into chemistry education, using the Nyamplung tree (Calophyllum inophyllum L.), part of the Sasak tribe’s knowledge, as teaching material. The study employed a pre-experimental pretest-posttest design with 17 chemistry students participating in three lab sessions. All course participants were selected as research subjects using purposive sampling. Performance was assessed through portfolios, and the N-gain method was used to analyze improvement. Results showed consistent performance increases, with scores rising from 75.52 to 87.76 over three sessions and N-gain values indicating positive but low-category improvement (0.015, 0.070, 0.181). These findings suggest that integrating ethnoscience-based materials can improve student performance while offering a culturally relevant learning experience.